2021
DOI: 10.1007/s00784-021-03863-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of 266 patients and family members with cleft lip and/or palate with associated malformations and syndromes

Abstract: Objectives To clinically characterize patients and family members with cleft lip and/or palate (CL/P) and associated congenital malformations or syndromes and propose possible inheritance patterns. Materials and methods An observational study of patients with CL/P, including medical and family history and intra- and extra-oral examination of their family members, was performed. Results Two hundred sixty-six patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The mean age of the NSCL±P children was ranged between 9-11 years. UCLP (51.3%) was the most common type of the cleft, which was in agreement with other study reported that UCL/P represent 65.7% of individuals with cleft lip/ palate in Berlin [10].…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of the NSCL±P children was ranged between 9-11 years. UCLP (51.3%) was the most common type of the cleft, which was in agreement with other study reported that UCL/P represent 65.7% of individuals with cleft lip/ palate in Berlin [10].…”
Section: Discussionsupporting
confidence: 92%
“…Sometimes, cleft defects are associated with other syndromes, as shown in a 2021 study [ 26 ] where cleft accompanied by syndromes represented 24 out of 266 cases. However, our results showed that only 2 out of 132 patients had cleft defects associated with syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a Colombian study found CL to be the most common type of cleft [ 30 ]. Furthermore, genetic factors play a crucial role in CL/P occurrence, and a positive family history increases the risk of cleft manifestation [ 8 , 31 34 ]. Compared to the international literature, the percentage of patients with a positive family history in the present study sample was rather low.…”
Section: Discussionmentioning
confidence: 99%